FROM SATISFACTION TO COMMITMENT: INVESTIGATING THE EFFECTS OF WORK ENVIRONMENT AND TRAINING ON SENIOR HIGH SCHOOL TEACHERS IN WEST SUMBA - Sukur, Paulinus; Sitaniapessy , Arthur; Hadiwidjaja, Rini Dwiyani (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: This study examines how the work environment and training influence job satisfaction and organizational commitment among senior high school teachers in West Sumba, addressing gaps in previous research by analyzing job satisfaction as a mediating variable.Methods: This study employed a quantitative approach using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the relationships among work environment, training, job satisfaction, and organizational commitment. Data were collected through a structured questionnaire administered to 84 senior high school teachers in West Sumba Regency, selected using a proportional stratified random sampling method.Results: The findings show that both the work environment and training have positive and significant effects on job satisfaction and organizational commitment. Training emerged as the strongest predictor of job satisfaction, and job satisfaction significantly mediated the effects of both the work environment and training on organizational commitment. All seven hypotheses were supported based on the SEM-PLS analysis.Conclusion and suggestion: The study concludes that improving the work environment and providing effective training are essential strategies for increasing teacher job satisfaction and strengthening organizational commitment. Job satisfaction plays a key mediating role in transforming these improvements into higher levels of teacher loyalty and dedication. It is suggested that schools prioritize professional development and create supportive working conditions to enhance teacher well-being and commitment. Keywords: Work Environment, Investigating, Satisfaction